Serum Levels of Soluble ST2 and IL-10 Are Associated with Disease Severity in Patients with IgA Nephropathy. (9th November 2016) - Zhang, Zhihui; Wang, Haifeng; Zhang, Li; Crew, Rebecca; Zhang, Nan; Liu, Xiaolei; Jiang, Yanfang
Abstract : Background . The IL-33/ST2 axis is involved in humoral immune responses. Method . The concentrations of sera IL-33 and sST2 in 74 patients and 34 healthy controls (HC) were measured by ELISA. Clinical and laboratory data were examined. The potential association between sera IL-33 and sST2 and the clinical parameters in IgAN patients were analyzed. Results . No difference was discovered in IL-33 concentrations between IgAN patients and HCs; however, the sST2 were significantly higher in each stage of IgAN progression than in the HC. The concentration of sST2 was positively correlated with IL-33 levels in IgAN patients. Higher levels of sera IL-2, IL-4, IL-10, IL-17A, and IFN- γ were detected in patients compared to the HC. The concentration of serum sST2 was positively correlated with the levels of IL-10 in IgAN patients. Furthermore, serum sST2 was negatively correlated with the values of eGFR and serum calcium. Serum sST2 was positively correlated with 24-hour urinary protein, serum phosphorus, and serum IgA; however, serum IL-33 was not associated with these. Following treatment, serum sST2 was significantly decreased, while sera IL-4 and IL-10 were significantly increased. Conclusions . Increased sST2 and IL-10 but not IL-33 may be involved in the pathogenic process of IgAN.